2001
DOI: 10.4049/jimmunol.166.12.7165
|View full text |Cite
|
Sign up to set email alerts
|

Sanglifehrin A, a Novel Cyclophilin-Binding Compound Showing Immunosuppressive Activity with a New Mechanism of Action

Abstract: We report here on the characterization of the novel immunosuppressant Sanglifehrin A (SFA). SFA is a representative of a class of macrolides produced by actinomycetes that bind to cyclophilin A (CypA), the binding protein of the fungal cyclic peptide cyclosporin A (CsA). SFA interacts with high affinity with the CsA binding side of CypA and inhibits its peptidyl-prolyl isomerase activity. The mode of action of SFA is different from known immunosuppressive drugs. It has no effect on the phosphatase activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
126
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 58 publications
8
126
1
2
Order By: Relevance
“…Similar to CsA, SFA binds to cyclophilin with high affinity. Unlike CsA, however, the cyclophilin-SFA complex has no effect on the phosphatase activity of calcineurin (21). Although SFA was shown to inhibit mouse and human mixed lymphocyte reactions (19), we and others have recently found that SFA does not affect T cell receptor-mediated signal transduction pathways leading to the production of cytokines such as IL-2 (21,22).…”
mentioning
confidence: 82%
“…Similar to CsA, SFA binds to cyclophilin with high affinity. Unlike CsA, however, the cyclophilin-SFA complex has no effect on the phosphatase activity of calcineurin (21). Although SFA was shown to inhibit mouse and human mixed lymphocyte reactions (19), we and others have recently found that SFA does not affect T cell receptor-mediated signal transduction pathways leading to the production of cytokines such as IL-2 (21,22).…”
mentioning
confidence: 82%
“…Studies of the immunosuppressive effects of SFA have been focused on T and B lymphocytes (5,6). Thus, SFA inhibits IL-2-induced T cell proliferation and mitogen-induced B cell proliferation (5,6). Similar to Rapa, SFA has been shown to inhibit cell cycle progression of T cells at the G 1 phase (7).…”
mentioning
confidence: 99%
“…SFA has been reported to exhibit lower immunosuppressive activity in the MLR when compared with CsA (1,5). Studies of the immunosuppressive effects of SFA have been focused on T and B lymphocytes (5,6). Thus, SFA inhibits IL-2-induced T cell proliferation and mitogen-induced B cell proliferation (5,6).…”
mentioning
confidence: 99%
See 2 more Smart Citations